CHARACTERISTICS OF REEF FISH COMMUNITIES RECORDED IN BACH LONG VI, CON CO, CON DAO AND PHU QUOC ISLANDS - Thu, Dao Duy; Thuoc, Pham (Vietnam Journal of Marine Science and Technology, 2009)
About 24,000 individuals reef fishes were analyzed and recorded by under water visual census and sampling at four locations where is representative forVietnamese seawaters including Tonkin Gulf (Bach Long Vi and Con Co Islands). South East region (Con Dao Island) and South West region (Phu Quoc Island) from 2006 to 2008. Based on bio-statistics methods, the studied results illustrated th e semi- tropical characteristics of the reef fish communities in the northern part (Tonkin Gulf) and tropical characteristics of the others in the southern part (including South-Eastern and South - Western regions). Each surveyed community was composed by many species and its species sim ilarity in dex was unequal. Th e study also proved the separation and vulnerability ofreeffis hes and confirmed that Pomacentrid and Labrid were most dominant in the surveyed sites. Almost reef fishes there belonged to small size species and certainly limited in foodstuff value. These assessments will be considered as th e basis for policy maker on reef fish management andexploitation effectiveness after Marine Protected Area (MPA) model is installed to these locations.